(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotatsiya: Adabiyot – bu faqat matn emas, balki his-tuyg‘u va tasavvurdir. Multimediadan (audio, video, grafikalar) foydalanish orqali badiiy asarlar o‘quvchilarga jonli va tushunarli ko‘rinishda taqdim etiladi. Ayniqsa, til o‘rganuvchilar uchun bu yondashuv nafaqat o‘qishni osonlashtiradi, balki talaffuz, madaniyat va ohangni ham o‘rganishga yordam beradi. Ushbu maqola multimediadan adabiy darslarda foydalanish usullarini ko‘rib chiqadi. Аннотация: Литература оживает через мультимедиа: видеоролики, аудиозаписи, иллюстрации усиливают эмоциональное восприятие текста. Особенно в обучении языкам, такой подход помогает учащимся лучше понять смысл, культуру и интонации. Статья анализирует эффективные способы внедрения мультимедиа в уроки литературы. Abstract: Literature is not just about reading printed words—it is about feeling, seeing, and imagining worlds. With today’s access to multimedia—video clips, audio recordings, visual art—teachers can turn reading into an immersive experience. For language learners, this multisensory exposure helps them not only understand the text but feel its tone, grasp character emotions, and learn pronunciation. Multimedia also aids comprehension for students with different learning styles. This paper examines how multimedia can enhance literature lessons, making texts more vivid, accessible, and engaging for 21st-century learners.